Impact Of Hospital Acreditation: Qualitative Study To Nurses In RSUD KRT Setjonegoro Of Wonosobo - Murti Mandawati; Muhammad Jauhar Fu'adi; Jaelan Jaelan (NURSCOPE: Jurnal Penelitian dan Pemikiran Ilmiah Keperawatan, 2018)
Introduction: As stated by the Ministry of Health, hospital accreditation is mandatory done through a series of assessments and improvements as a step to ensure the hospital in prioritizing public services, safety and protection. Nursing care as one of the main services in hospitals is the most widely rated service in accreditation. Therefore, this study was done to determine the nurse's perception of the impact of accreditation on nursing. Methodology: This qualitative study examined 21 hospital nurses as its respondents. The data were collected by in-depth interviews using interview guides. The data were then analyzed and categorized to determine the theme. Results: According to the nurses, hospital accreditation was important to implement. The positive impacts of accreditation were the increased care of nurses on patient safety indicators, among others, improvements in the problem reporting flow, compliance with standard operating procedures, communication among health workers, documentation, service facilities,continuing nurses education, health education, and working enviroument. Discussion: a positive outlook on accreditation activities is a good start for hospitals to continue to improve service quality. Because the main thing in service is the quality of service assessed from the clinical indicators of the service, not the completeness of the documentation.